2012
DOI: 10.1002/chem.201203012
|View full text |Cite
|
Sign up to set email alerts
|

A New Series of C‐6 Unsubstituted Tetrahydropyrimidines: Convenient One‐Pot Chemoselective Synthesis, Aggregation‐Induced and Size‐Independent Emission Characteristics

Abstract: A new series of C-6 unsubstituted tetrahydropyrimidines 6 have been directly synthesized via a convenient urea-catalyzed chemoselective five-component reaction (5CR) under mild conditions. Compounds 6 show typical aggregation-induced emission enhancement (AIEE) characteristics because they are practically no emissive in solution but emit blue or green fluorescence in aggregates with fluorescence yield up to 93%. One of the 5CR products, 6aa, exhibits blue- and green-fluorescence aggregates (bf- and gf-aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 168 publications
2
48
0
1
Order By: Relevance
“…It has been reported that some synthetic non‐aromatic macromolecules, such as poly[(maleic anhydride)‐ alt ‐(vinyl acetate)] and vinyl polymers carrying succinic anhydride terminal groups, are also highly luminescent. Apart from these big macromolecules, some small molecules without classical chromophores have been found to show AIE activity . Zhu et al, for example, have synthesized a class of tetrahydropyrimidine derivatives with AIE characteristics .…”
Section: Structure Diversificationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that some synthetic non‐aromatic macromolecules, such as poly[(maleic anhydride)‐ alt ‐(vinyl acetate)] and vinyl polymers carrying succinic anhydride terminal groups, are also highly luminescent. Apart from these big macromolecules, some small molecules without classical chromophores have been found to show AIE activity . Zhu et al, for example, have synthesized a class of tetrahydropyrimidine derivatives with AIE characteristics .…”
Section: Structure Diversificationmentioning
confidence: 99%
“…Apart from these big macromolecules, some small molecules without classical chromophores have been found to show AIE activity . Zhu et al, for example, have synthesized a class of tetrahydropyrimidine derivatives with AIE characteristics . Luminogen 47 , for instance, is non‐emissive in solutions but becomes highly luminescent when aggregated.…”
Section: Structure Diversificationmentioning
confidence: 99%
See 1 more Smart Citation
“…If the fluorescence changes are very sharp and visible about/at CMC, the CMC values will be directly observed. In 2011 [18], we developed an efficient five-component reaction for the synthesis of a novel series of C6-unsubstituted tetrahydropyrimidines (THPs) with strong aggregation-induced emission (AIE) characteristics, that is, no emission in solution but strong fluorescence in aggregates. AIE characteristic, found and termed by Tang's group [19], resolves the thorny aggregation-caused quenching problem of conventional fluorophores and has shown great advantages in wide areas [20], such as AIEgens-containing copolymers and their applications [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This view is also supported by more recent work of Zhu et al., who have examined a large series of tetrahydropyrimidines in which N‐1 has both alkyl and 4‐substituted aryl groups. They found that both types of substituents resulted in H‐6a/H‐6b geminal coupling constants in the range of −17.6 to −18.0 Hz …”
Section: Resultsmentioning
confidence: 99%